MODEL CORPORATE SOCIAL RESPONSIBILITY (CSR) PERUSAHAAN TAMBANG BATUBARA DI KABUPATEN LAHAT TERHADAP PEMBERDAYAAN MASYARAKAT BERBASIS KEARIFAN LOKAL - Antonius Suhadi; AR Febrian; Sri Turatmiyah (Jurnal Dinamika Hukum, 2014)
Corporate Social Responsibility  (CSR) is a corporate responsibility. The research intends to inves-tigate how CSR program is implemented, the role of local administrative, and CSR alternative model on the coal mining company in Lahat District. This normative and empiric research is aimed at finding out the implementation of local government role, and to find out the alternative model of CSR. The CSR implementation of PT BA and PT BAU as a mining company in the cooperation program includes area and environmental development. The CSR program on community development, as the result of agreement among mining company, local people and related agency has to be based on the approval of local administrative. The best alternative model CSR is the collaborative model among corporation, local government and local people. Key words: corporate social responsibility, community development, collaborative model.